Design, Development, and Evaluation of Controlled Release Tablets of Nateglinide Solid Dispersions - Sunitha, Ramisetty (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: The current study deals with formulation and evaluation of nateglinide solid dispersion (SD) incorporate into tablet formulation for controlled release of the drug. Methods: The nateglinide SD prepared using crospovidone and evaluated for drug content and drug dissolution. The optimized SD formulation incorporated into tablet using HPMC K100 and Cederela gum. All the tablet formulations evaluated for pre-compression, post-compression, drug dissolution, and excipient compatibility study. Results: The formulation SD15 comprising of drug, crospovidone, and sodium lauryl sulfate in 1:3:2 ratio displayed 48-fold enhancement in drug solubility when compared to pure drug. The formulation SD15 displayed maximum yield of 98.96% and maximum drug content of 99.68% chosen optimal for tablet formulation. Fourier transforms infrared studies revealed that there is no incompatibility between drug and polymers found. X-Ray diffractometer studies revealed that the optimized SD formulation was found to be in amorphous state. Total 15 formulations of controlled release tablet blends evaluated for micrometric properties show that all the formulations possess good flow properties F12 formulation with maximum drug content of 99.93% and drug release of 99.98% over 16 h was chosen for further characterized. The release kinetics suggest that drug release followed zero order and release from tablets was anomalous non-Fickian diffusion super Case II transport. Conclusion: The combination of SD and application of hydrophilic and hydrophobic polymers in matrix formation facilitated superior dissolution and absorption profile with greater patient compliance.